Oil and Gas Terminology in Explanatory Dictionaries - Jamalova Dilafruz Komiljon Qizi (Universal Teaching and Learning Journal, 2026)
Purpose: This study aims to examine how oil and gas terminology is presented in explanatory dictionaries of the Uzbek language. This study seeks to understand how these dictionaries define, simplify, and standardize technical terms within the general language system. Research Methodology: This study used a qualitative lexical analysis of printed and digital Uzbek explanatory dictionaries. A descriptive and comparative approach was applied to examine the definitions, meanings, polysemy, stylistic features, and normative aspects of oil and gas terms through document and textual reviews. Results: The findings show that explanatory dictionaries present oil and gas terms in a simplified and generalized way. Although they provide normative and lexical meanings, they often do not fully reflect the scientific and technical depth of the terms. The analysis also revealed the presence of polysemy, stylistic neutrality, and the integration of oil and gas terminology into the broader general language system. Conclusions: This study concludes that explanatory dictionaries play an important normative role in standardizing oil and gas terminology in the Uzbek language. However, their definitions are limited in representing the full scientific and technical complexity of specialized terminology. Limitations: This study is limited to explanatory dictionaries of the Uzbek language and does not include encyclopedic dictionaries or specialized technical glossaries for comparison. Contributions: This study contributes to lexicography, terminology studies, and applied linguistics. It is useful for linguists, lexicographers, oil and gas specialists, and language planners interested in the development and standardization of technical terminology in Uzbek and other languages.